2020
DOI: 10.1055/s-0040-1701234
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Infection Control: Clostridioides difficile

Abstract: Clostridioides difficile remains a leading cause of healthcare-associated infection. Efforts at C. difficile prevention have been hampered by an increasingly complex understanding of transmission patterns and a high degree of heterogeneity among existing studies. Effective prevention of C. difficile infection requires multimodal interventions, including contact precautions, hand hygiene with soap and water, effective environmental cleaning, use of sporicidal cleaning agents, and antimicrobial stewardship. Role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 124 publications
0
17
0
Order By: Relevance
“…Clostridioides ( Clostridium ) difficile is a spore-forming, gram-positive, and anaerobic bacillus found in the environment and in the intestinal tract of animals and humans. In humans, the infection is the leading cause of antibiotic-associated diarrhea and of a wide range of gastrointestinal syndromes ( Knight et al, 2015 ; Turner and Anderson, 2020 ). The molecular epidemiology of C. difficile infection (CDI) has shown that the bacterial genome and the disease have become very variable in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Clostridioides ( Clostridium ) difficile is a spore-forming, gram-positive, and anaerobic bacillus found in the environment and in the intestinal tract of animals and humans. In humans, the infection is the leading cause of antibiotic-associated diarrhea and of a wide range of gastrointestinal syndromes ( Knight et al, 2015 ; Turner and Anderson, 2020 ). The molecular epidemiology of C. difficile infection (CDI) has shown that the bacterial genome and the disease have become very variable in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Antibiotic exposure is the most common trigger, as it disrupts the normal bowel flora. 25 Though most of the older studies do not mention C. difficile , Grover et al terminated their study early due to concerns from recent publications linking clindamycin usage to C. difficile infections. 11 Most recently, Cook et al reported no difference in C. difficile colitis between the antibiotic prophylaxis and control groups, which is consistent with reported increases in community-acquired cases.…”
Section: Discussionmentioning
confidence: 99%
“…First, this could reflect a commitment by health care organizations in reducing the infection rates by taking increasingly aggressive measures to prevent CDI. Adherence to infection control measures, such as handwashing, contact precautions, and patient isolation, environmental screening and cleaning, and the use of sporicidal germicides, [21][22][23] may have improved over time and are potentially modifiable with hospital-based initiatives. For example, Vaughn et al 24 found an increase in reported use of infection prevention practices against CDI in Veterans Affairs hospitals.…”
Section: Discussionmentioning
confidence: 99%